TEORI RELASIONAL HUBUNGAN AGAMA-NEGARA: PRAKTIK REGULASI DAN POSISI ISLAM DI ARAB SAUDI, MALAYSIA DAN TURKI (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Debates on religion-state relations have long been dominated by the dichotomy between secularism and theocracy, framing the state either as neutral toward religion or as governed by religious authority. This binary framework, however, fails to adequately capture the complex regulatory practices observed in Muslim-majority countries, where Islam continues to shape legal, political, and institutional arrangements in diverse ways. Existing scholarship largely focuses on constitutional status and ideological orientation, while overlooking regulation as a dynamic arena of power, negotiation, and legitimacy. This article addresses this gap by proposing a relational religion-state theory and applying it to a comparative socio-legal analysis of religious regulation in Saudi Arabia, Malaysia, and Turkey. By examining constitutional arrangements, legal-institutional mechanisms, and policy practices, the study analyzes how regulation functions as an indicator of relational configurations between state authority and religious institutions. The findings demonstrate that religion-state relations in these countries cannot be reduced to secular or theocratic models. Saudi Arabia exhibits a dominative configuration, Malaysia an accommodative-instrumental configuration, and Turkey a coercive yet evolving configuration. The article contributes theoretically by advancing a relational framework that transcends conventional dichotomies and empirically by offering a systematic mapping of religion-state governance in Muslim contexts.